Status Gizi dan Perilaku Makan Ibu Selama Kehamilan Trimester Pertama - Ambar Kusuma Dewi; Dary Dary; Rifatolistia Tampubolon (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2021)
Background: Nutritional problems in Indonesia are one of the indirect causes of maternal and child mortality. The low nutritional status of mothers before pregnancy and during the first trimester of pregnancy results in babies with low birth weight, stunting and prematurity, pregnancy in the first trimester is the most vulnerable period, where the process of forming very important organs such as the central nerve, heart and hearing is enhanced in the next trimester.Methods: This research uses descriptive quantitative design. Respondents of the study were 50 pregnant women in the first trimester in the Salatiga Primary Health Care. Nutritional status was determined by weight gain of respondents during pregnancy, while eating behavior was measured using the SQ-FFQ Form. The 2x24 hour food recall was used to determine the level of nutritional intake of respondents.Result: The results showed that the respondents experienced a deficit of TKP, TKE, and TKK and TKL excess, while the abnormal weight gain was 44%, and KEK was 20%.Conclusion : Respondents experienced nutritional problems because their daily food intakes were less than their needs